A carbon fiber-polydicyclopentadiene composite material with high notched impact strength and its preparation and application
By using effective composite of dicyclopentadiene resin and carbon fiber material, the difficulties of carbon fiber composite materials in mechanical processing are solved, high notch impact strength and good processing performance are achieved, and their application fields are expanded.
Patent Information
- Application Number
- CN202510020986.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-01
AI Technical Summary
The existing carbon fiber composite materials have poor affinity with polymer resins, and pores and gaps are prone to appear during the composite process, resulting in difficulty in mechanical processing.
A bicyclopentadiene resin material with excellent performance is effectively combined with the carbon fiber material, and a carbon fiber-polybicyclopentadiene composite material with high notch impact strength is prepared through a reaction molding process, without the need for surface modification of the carbon fiber.
The high notch impact strength and good mechanical processing performance of carbon fiber composite materials are achieved, which simplifies the preparation process, reduces costs, and expands the application prospects.
Smart Images

Figure CN119735909A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a polydicyclopentadiene / carbon fiber composite material and a preparation method thereof. Background Art
[0002] Carbon fiber reinforced polymer (CFRP) is an advanced material composed of carbon fiber and polymer resin. It has excellent mechanical properties and its density is much lower than that of traditional metal materials. In addition, carbon fiber composites also have excellent corrosion resistance, thermal stability and fatigue resistance. They are widely used in aerospace, automotive industry, sporting goods, construction engineering, military and national defense. In recent years, my country's carbon fiber production capacity has continued to increase, production costs are gradually decreasing, and the application field of carbon fiber composites is expanding. However, carbon fiber composites still face some challenges in large-scale applications.
[0003] Existing carbon fiber composite materials are mainly carbon fiber epoxy resin materials. The impact toughness of the composite materials is poor. When subjected to external impact or long-term load, brittle fracture and splitting will occur. This phenomenon will significantly reduce the mechanical properties of the material and eventually lead to structural failure. The poor toughness and high viscosity of the selected polymer resin material, as well as the bubbles and voids present in the composite process with carbon fiber are the main reasons for this phenomenon. This structural attribute causes carbon fiber composite materials to have a low tolerance for internal damage. Compared with metal materials, once damage occurs, the cracks formed will rapidly expand and cause material failure. Therefore, existing carbon fiber composite materials are extremely difficult to process, with poor design flexibility. Processing requires special equipment and technology, which increases the cost of the final product and greatly limits the application of carbon fiber composite materials.
[0004] Polydicyclopentadiene (PDCPD) is a novel thermosetting engineering plastic, a thermosetting engineering material with high strength, high modulus and high impact strength, which can be prepared by ring-opening metastasis polymerization of dicyclopentadiene (DCPD). Dicyclopentadiene is a C5 fraction of petroleum cracking, with low cost, and its bulk solution viscosity is very small, which has great advantages in preparing composite materials, but dicyclopentadiene (DCPD) is usually polymerized at a fast rate, and can be cured and formed in a short time, and this feature is very unfavorable for the preparation of composite materials. At the same time, the sizing agent on the surface of carbon fiber material is generally a polar substance such as epoxy compounds, which has poor affinity with polydicyclopentadiene, and the performance of the obtained composite material will also be greatly discounted.
[0005] Therefore, developing a new type of dicyclopentadiene resin solution, controlling its polymerization rate, improving its affinity with polar substances such as epoxies, and enhancing the comprehensive performance of composite materials are of positive significance for the manufacture of carbon fiber-polydicyclopentadiene composite materials. Summary of the invention
[0006] The purpose of the present invention is to solve the problem that the existing carbon fiber composite materials are difficult to machine due to the low affinity between the carbon fiber material and the polymer resin, and the air holes and gaps are easily formed during the composite process, thereby providing a machineable carbon fiber-polydicyclopentadiene composite material and its application. In view of this key technical problem, the present invention proposes a dicyclopentadiene resin material with excellent performance, which can be effectively composited with the carbon fiber material to prepare a carbon fiber composite material with excellent comprehensive performance (especially notched impact strength), and the material can be subjected to a variety of mechanical processing.
[0007] The technical solution of the present invention:
[0008] A machine-processable carbon fiber-polydicyclopentadiene composite material with high notched impact strength, the composite material is compounded by carbon fiber fabric and resin liquid through a reaction molding process, wherein the raw material mass ratio of carbon fiber fabric to resin liquid is (1.0-5.0):1, and the further preferred mass ratio is (2.5-5.0):1; the resin liquid is prepared by mixing dicyclopentadiene, resin additive, interface agent, catalyst and catalyst additive. The composite material can be machined, specifically including turning, milling, drilling, grinding, planing, boring, sawing, tapping and other processing methods.
[0009] In some embodiments, the strength grade of the carbon fiber fabric is one or more of T300, T700, T800 grade carbon fiber cloth and carbon fiber cloth fiber bundles, and the warp and weft yarn bundles are 3k, 6k or 12k; the carbon fiber fabric is one or more of plain carbon fiber cloth, twill carbon fiber cloth and satin carbon fiber cloth.
[0010] In some embodiments, the resin liquid contains 72.917wt%-90.931wt% of dicyclopentadiene, 4.205wt%-15.678wt% of resin additives, 2.162wt%-5.536wt% of interface agent I, 2.532wt%-5.833wt% of interface agent II, 0.005wt%-0.028wt% of catalyst, and 0.050wt%-0.500wt% of catalyst additives (including retarder and cosolvent). The resin additive is used to improve the viscosity of the liquid so that the initial viscosity of the resin will not be too thin or too viscous, and the olefin component can improve the cross-linking strength of the resin and improve the strength of the resin; the interface agent is used to improve the affinity between the resin and the surface of the carbon fiber, and the alcohol substance in the interface agent I will react with the isocyanate in the interface agent II to improve the comprehensive performance of the composite material; the catalyst additive is used to dissolve the catalyst and reduce the initial polymerization rate so that the initial viscosity of the resin will not be too large to hinder the injection of the resin.
[0011] In some embodiments, the resin additive is 5-vinylbicyclo[2.2.1]hept-2-ene, ethylidene norbornene and phenyl olefin molecules; the mass ratio of the three is 1:(80-200):(5-20); the phenyl olefin molecules are one or more of the following structures:
[0012]
[0013] The R group is a C1-C6 alkyl group.
[0014] In some embodiments, the interface agent I comprises an alcohol substance and an initiator, and the mass ratio of the two is 1: (0.3-3); the alcohol substance comprises one or more of the following structures, wherein the degree of polymerization of the polymer n=5-50:
[0015]
[0016] The initiator is one or more of dioxane, polyoxane, and peroxide; the peroxide includes one or more of the following structures:
[0017]
[0018] In some embodiments, the interface agent II comprises an epoxy compound and an isocyanate, and the mass ratio of the epoxy compound and the isocyanate is 1: (30-100); the epoxy compound comprises glycidyl methacrylate 4,5-Epoxytetrahydrophthalic acid diglycidyl ester Cyclohexane-1,2-dicarboxylic acid diglycidyl ester and diglycidyl tetrahydrophthalate One or more of the following;
[0019] The isocyanate is one or more of the following structures:
[0020]
[0021] In some embodiments, the catalyst is a ruthenium complex and an organic tin compound, wherein the mass ratio of the ruthenium complex to the organic tin compound is 1:(0.1-5); the ruthenium complex comprises one or more of the following structures:
[0022]
[0023] The organotin compound comprises one or more of the following structures:
[0024]
[0025] Ruthenium complexes are used to catalyze the polymerization of dicyclopentadiene and related olefin compounds, and organotin compounds are used to catalyze the reaction of alcohols and isocyanates.
[0026] In some embodiments, the catalyst promoter comprises a retarder and a cosolvent, and the mass ratio of the two is 1:(3-10); wherein the retarder is a phosphite molecule, specifically one or more of trimethyl phosphite, triethyl phosphite, tripropyl phosphite, tributyl phosphite, triphenyl phosphite or tritolyl phosphite; the cosolvent is one or more of diphenyl ether, dihydroindane, indene, tetralin, trichlorobenzene, phenylcyclopropane, and benzocyclobutane.
[0027] The present invention also provides a method for preparing the carbon fiber-polydicyclopentadiene composite material, comprising the following steps:
[0028] A1 prepares raw materials according to the above stoichiometric ratio, takes a portion of dicyclopentadiene, resin additives and interface agent I and mixes them thoroughly to prepare a uniform solution to obtain modified dicyclopentadiene resin solution I;
[0029] A2 fully mixes the remaining dicyclopentadiene with the interface agent II to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution II
[0030] A3 fully mixes the catalyst, the cosolvent in the catalyst promoter and the retarder to obtain a catalyst solution;
[0031] A4: First lay a release cloth in the mold, stack multiple layers of carbon fiber fabric on the release cloth, then lay another release cloth on the carbon fiber fabric, then close the mold, and blow nitrogen or argon along the injection port to drive out the residual air in the mold;
[0032] A5: uniformly mix the modified dicyclopentadiene resin liquid I, the modified dicyclopentadiene resin liquid II and the catalyst solution to obtain a resin liquid, inject the obtained resin liquid into the mold cavity along the injection port, then heat it to 80-180° C., keep it warm for 0.5-8 hours to complete curing, and demold to obtain the carbon fiber-polydicyclopentadiene composite material.
[0033] The selection ranges of the raw carbon fiber fabric and dicyclopentadiene, resin additive, interface agent I, interface agent II, catalyst and catalyst additive in the resin solution in the preparation method are the same as above.
[0034] In some embodiments of the present invention, the tensile strength of the composite material is 624-1092 MPa.
[0035] In some embodiments, the flexural strength of the composite material is 603-840 MPa; and the flexural modulus of the composite material is 48-98 GPa.
[0036] In some embodiments, the interlaminar shear strength of the composite material is 47-65 MPa.
[0037] In some embodiments, the composite material has a notched impact strength of 68-169 KJ m -2 .
[0038] In some embodiments, the composite material has a post-impact compressive strength of 170-262 MPa.
[0039] In some embodiments, the composite material has an open hole tensile strength of 380-485 MPa;
[0040] In some embodiments, the composite material has an open-hole compressive strength of 288-367 MPa.
[0041] In some embodiments of the present invention, the composite material can be machined, including turning, milling, drilling, grinding, planing, boring, sawing, and tapping, and can be applied to the automotive industry, rail transportation, construction industry, aerospace, sporting goods, storage and packaging and other fields.
[0042] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in the present invention. (In the following specific embodiments, the various technical solutions can be combined with each other in principle to obtain new technical solutions, which should also be regarded as specifically disclosed in the present invention.)
[0043] Advantages and beneficial effects of the present invention:
[0044] The present invention discloses a carbon fiber-polydicyclopentadiene composite material and a preparation method and application thereof. The carbon fiber composite material is prepared by curing and molding carbon fiber and dicyclopentadiene resin liquid after compounding. The dicyclopentadiene resin liquid has the advantages of moderate viscosity, controllable polymerization mode, and easy source of raw materials. The composite material preparation method does not require surface modification of carbon fiber, and the operation process is simple. The obtained composite material has excellent comprehensive performance, especially high notched impact strength, and can be machined, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0046] Figure 1 .Microscopic comparison of the cross-section of the carbon fiber composite material after cutting; the left picture is a microscopic picture of the cross-section of the composite material prepared based on Comparative Example 4, and the right picture is a microscopic picture of the cross-section of the composite material prepared based on Example 1 of the present invention.
[0047] Figure 2. Photographs of samples of the carbon fiber composite material prepared according to Example 1 of the present invention after drilling and tapping.
[0048] Figure 3 . Actual load picture of the carbon fiber composite material after processing prepared according to Example 1 of the present invention; the left picture is a photo of the riveting load, the right picture is a photo of the bolt load, and the embedded picture is an enlarged picture of the bolt part.
[0049] Figure 4 . Actual pictures of CNC cutting and CNC carving of the carbon fiber composite material prepared according to Example 1 of the present invention. DETAILED DESCRIPTION
[0050] [Example 1]
[0051] A1, 1000g of dicyclopentadiene, 131g of resin additive (comprising 120g of ethylidene norbornene, 0.9g of vinyl bicyclo [2.2.1] hept-2-ene, 10g of 1,3-diisopropylbenzene and 0.1g of 2-isopropoxystyrene) and 68g of interface agent I (comprising 12g of polyethylene glycol and 12g of 5-norbornene-2-methanol, 39g of diisopropyl peroxide and 5g of dimethicone) were fully mixed to prepare a uniform solution to obtain modified dicyclopentadiene resin solution I;
[0052] A2, secondly, 300 g of dicyclopentadiene and 61 g of interface agent II (comprising 40 g of polymerized MDI, 20 g of 3,4-MDI and 1.0 g of glycidyl methacrylate) were fully mixed to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution II;
[0053] A3, 0.065g 0.10 g of monobutyltin triisooctanoate, 1.80 g of diphenyl ether and 0.40 g of tricresyl phosphite were fully mixed to obtain a catalyst solution;
[0054] A4. Lay the release cloth in the mold first, and then stack T300 grade twill carbon fiber fabric on the release cloth. The warp and weft yarns of the carbon fiber fabric are 3k. Then lay the release cloth on the carbon fiber fabric, and then close the mold, and blow nitrogen or argon along the injection port to drive out the residual air in the mold;
[0055] A5. Evenly mix the modified dicyclopentadiene resin liquid I, the modified dicyclopentadiene resin liquid II and the catalyst solution to obtain a resin liquid, and inject the obtained resin liquid into the mold cavity along the injection port, then heat it to 150°C, keep it warm for 2.5 hours to complete curing, and demold to obtain a carbon fiber-polydicyclopentadiene composite material, wherein the mass ratio of the carbon fiber fabric to the resin liquid is 2.5:1.
[0056] [Example 2]
[0057] 1000 g of dicyclopentadiene, 61 g of a resin auxiliary (comprising 55 g of ethylidene norbornene, 0.4 g of vinyl bicyclo[2.2.1]hept-2-ene, and 5.6 g of 1,4-diisopropenylbenzene) and 31 g of an interface agent I (comprising 12 g of polypropylene glycol and 12 g of 5-norbornene-2-methanol, 6 g of tert-butyl peroxide and 1 g of polydioxane) were fully mixed to prepare a uniform solution, thereby obtaining a modified dicyclopentadiene resin solution I;
[0058] Secondly, 310 g of dicyclopentadiene and 37 g of interface agent II (comprising 36 g of polymerized PPDI and 1.0 g of cyclohexane-1,2-dicarboxylic acid diglycidyl ester) were fully mixed to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution II;
[0059] 0.055g 0.018 g of monobutyltin triisooctanoate, 1.20 g of tetralin and 0.25 g of tripropyl phosphite were fully mixed to obtain a catalyst solution;
[0060] A demoulding cloth is first laid in the mold, and a T300-grade plain carbon fiber fabric is stacked on the demoulding cloth, the warp and weft yarn bundles of the carbon fiber fabric are 6k, and then a demoulding cloth is laid on the carbon fiber fabric again, and then the mold is closed, and nitrogen or argon is blown into the mold along the injection port to drive out the residual air in the mold; modified dicyclopentadiene resin liquid I, modified dicyclopentadiene resin liquid II, and catalyst solution are uniformly mixed to obtain a resin liquid, and the obtained resin liquid is injected into the mold cavity along the injection port, and then the temperature is raised to 110°C, and the temperature is kept for 5.5 hours to complete curing, and the carbon fiber-polydicyclopentadiene composite material is obtained by demoulding, wherein the mass ratio of the carbon fiber fabric to the resin liquid is 3.8:1.
[0061] [Example 3]
[0062] First, 900 g of dicyclopentadiene, 110.8 g of a resin additive (comprising 100 g of ethylidene norbornene, 0.8 g of vinyl bicyclo[2.2.1]hept-2-ene, 9.95 g of 1,3-diisopropenylbenzene and 0.05 g of 2-isopropoxystyrene) and 38 g of an interface agent I (comprising 9 g of polyethylene glycol and 9 g of 5-norbornene-2-methanol, 16 g of diisopropyl peroxide and 4 g of dicumyl) were fully mixed to prepare a uniform solution, thereby obtaining a modified dicyclopentadiene resin solution I;
[0063] Secondly, 100 g of dicyclopentadiene and 50.8 g of interface agent II (comprising 50 g of polymerized MDI and 0.8 g of glycidyl methacrylate) were fully mixed to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution II;
[0064] Then 0.085g 0.10 g of monobutyltin triisooctanoate, 1.70 g of phenylcyclopropane, 0.85 g of indane and 0.50 g of tritolyl phosphite were fully mixed to obtain a catalyst solution;
[0065] A demoulding cloth is first laid in the mold, and a T700-grade plain carbon fiber fabric is stacked on the demoulding cloth, the warp and weft yarn bundles of the carbon fiber fabric are 6k, and then a demoulding cloth is laid on the carbon fiber fabric again, and then the mold is closed, and nitrogen or argon is blown into the mold along the injection port to drive out the residual air in the mold; modified dicyclopentadiene resin liquid I, modified dicyclopentadiene resin liquid II, and catalyst solution are uniformly mixed to obtain a resin liquid, and the obtained resin liquid is injected into the mold cavity along the injection port, and then the temperature is raised to 140°C, and the temperature is kept for 2 hours to complete curing, and the carbon fiber-polydicyclopentadiene composite material is obtained by demoulding, wherein the mass ratio of the carbon fiber fabric to the resin liquid is 3.5:1.
[0066] [Example 4]
[0067] 900 g of dicyclopentadiene, 123.4 g of a resin additive (comprising 112 g of ethylidene norbornene, 1.4 g of vinyl bicyclo[2.2.1]hept-2-ene and 10 g of styrene) and 60 g of an interface agent I (comprising 15 g of polytetrahydrofuran and 45 g of tert-butyl perbenzoate) were fully mixed to prepare a uniform solution, thereby obtaining a modified dicyclopentadiene resin solution I;
[0068] Secondly, 153 g of dicyclopentadiene and 46 g of interface agent II (comprising 25 g of XDI, 20 g of HDI and 1.0 g of cyclohexane-1,2-dicarboxylic acid diglycidyl ester) were fully mixed to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution II;
[0069] 0.075g 0.10 g of dioctyltin oxide, 0.6 g of trichlorobenzene and 0.20 g of tributyl phosphite were fully mixed to obtain a catalyst solution;
[0070] A demoulding cloth is first laid in the mold, and a T800-grade plain carbon fiber fabric is stacked on the demoulding cloth, the warp and weft yarn bundles of the carbon fiber fabric are 12k, and then a demoulding cloth is laid on the carbon fiber fabric again, and then the mold is closed, and nitrogen or argon is blown into the mold along the injection port to drive out the residual air in the mold; modified dicyclopentadiene resin liquid I, modified dicyclopentadiene resin liquid II, and catalyst solution are uniformly mixed to obtain a resin liquid, and the obtained resin liquid is injected into the mold cavity along the injection port, and then the temperature is raised to 90°C, and the temperature is kept for 7 hours to complete curing, and the carbon fiber-polydicyclopentadiene composite material is obtained by demoulding, wherein the mass ratio of the carbon fiber fabric to the resin liquid is 3.6:1.
[0071] [Example 5]
[0072] 1000 g of dicyclopentadiene, 105.5 g of a resin additive (comprising 100 g of ethylidene norbornene, 0.5 g of vinyl bicyclo[2.2.1]hept-2-ene and 5 g of 1,4-diisopropenylbenzene) and 70 g of an interface agent I (comprising 8 g of 2-hydroxyethyl acrylate, 12 g of polypropylene glycol, 30 g of tert-butyl perbenzoate and 20 g of polydioxane) were fully mixed to prepare a uniform solution, thereby obtaining a modified dicyclopentadiene resin solution I;
[0073] Secondly, 300 g of dicyclopentadiene and 76 g of interface agent II (comprising 75 g of IPDI and 1.0 g of diglycidyl tetrahydrophthalate) were fully mixed to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution II;
[0074] 0.28g 0.028 g of dioctyltin oxide, 0.67 g of indane and 0.10 g of tripropyl phosphite were fully mixed to obtain a catalyst solution;
[0075] A demoulding cloth is first laid in a mold, and a T800-grade twill carbon fiber fabric is stacked on the demoulding cloth, wherein the warp and weft yarn bundles of the carbon fiber fabric are 6k. Then, a demoulding cloth is laid on the carbon fiber fabric again, and then the mold is closed, and nitrogen or argon is blown into the mold along the injection port to drive away the residual air in the mold; modified dicyclopentadiene resin liquid I, modified dicyclopentadiene resin liquid II, and a catalyst solution are uniformly mixed to obtain a resin liquid, and the obtained resin liquid is injected into the mold cavity along the injection port, and then the temperature is raised to 125°C, and the temperature is kept for 4 hours to complete curing, and the carbon fiber-polydicyclopentadiene composite material is obtained by demoulding, wherein the mass ratio of the carbon fiber fabric to the resin liquid is 5.0:1.
[0076] [Example 6]
[0077] 850 g of dicyclopentadiene, 215.5 g of a resin additive (comprising 200 g of ethylidene norbornene, 1.5 g of vinyl bicyclo[2.2.1]hept-2-ene, 10 g of 1,4-diisopropenylbenzene and 4 g of 2-isopropoxystyrene) and 76 g of an interface agent I (comprising 18 g of polytetrahydrofuran, 12 g of polyethylene glycol, 23 g of dicyclopentane and 23 g of polydicyclopentane) were fully mixed to prepare a uniform solution, thereby obtaining a modified dicyclopentadiene resin solution I;
[0078] Secondly, 150 g of dicyclopentadiene and 80.8 g of interface agent II (comprising 50 g of polymerized MDI, 30 g of PPDI and 0.8 g of glycidyl methacrylate) were fully mixed to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution II;
[0079] 0.08g 0.3 g of di-n-butyltin diisooctanoate, 3.1 g of diphenyl ether, 3.1 g of indane, 0.6 g of trichlorobenzene and 0.64 g of tripropyl phosphite were fully mixed to obtain a catalyst solution;
[0080] A demoulding cloth is first laid in a mold, and a T700-grade plain carbon fiber fabric is stacked on the demoulding cloth, the warp and weft yarn bundles of the carbon fiber fabric are 3k, and then a demoulding cloth is laid on the carbon fiber fabric again, and then the mold is closed, and nitrogen or argon is blown into the mold along the injection port to drive out the residual air in the mold; modified dicyclopentadiene resin liquid I, modified dicyclopentadiene resin liquid II, and catalyst solution are uniformly mixed to obtain a resin liquid, and the obtained resin liquid is injected into the mold cavity along the injection port, and then the temperature is raised to 105°C, and the temperature is kept for 6 hours to complete curing, and the carbon fiber-polydicyclopentadiene composite material is obtained by demoulding, wherein the mass ratio of the carbon fiber fabric to the resin liquid is 1.0:1.
[0081] [Example 7]
[0082] 800 g of dicyclopentadiene, 153 g of a resin auxiliary (comprising 140 g of ethylidene norbornene, 1.0 g of vinyl bicyclo[2.2.1]hept-2-ene, and 12 g of 2-methoxystyrene) and 65 g of an interface agent I (comprising 10 g of polytetrahydrofuran, 10 g of 5-norbornene-2-methanol, 6 g of dicumyl and 39 g of diisopropylbenzene peroxide) were fully mixed to prepare a uniform solution, thereby obtaining a modified dicyclopentadiene resin solution I;
[0083] Secondly, 200 g of dicyclopentadiene and 61 g of interface agent II (comprising 40 g of 4,4-HMDI, 20 g of 3,4-MDI, 0.5 g of diglycidyl tetrahydrophthalate and 0.5 g of glycidyl methacrylate) were fully mixed to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution II;
[0084] 0.2g 0.025 g of dioctyltin dodecanoate, 0.025 g of dibutyltin diacetate, 1.8 g of trichlorobenzene, 1.8 g of indene, and 0.64 g of tripropyl phosphite were fully mixed to obtain a catalyst solution;
[0085] A demoulding cloth is first laid in the mold, and a T300-grade twill flat fiber fabric is stacked on the demoulding cloth, the warp and weft yarn bundles of the carbon fiber fabric are 12k, and then a demoulding cloth is laid on the carbon fiber fabric again, and then the mold is closed, and nitrogen or argon is blown into the mold along the injection port to drive out the residual air in the mold; modified dicyclopentadiene resin liquid I, modified dicyclopentadiene resin liquid II, and catalyst solution are uniformly mixed to obtain a resin liquid, and the obtained resin liquid is injected into the mold cavity along the injection port, and then the temperature is raised to 60°C, and the temperature is kept for 8 hours to complete curing, and the carbon fiber-polydicyclopentadiene composite material is obtained by demoulding, wherein the mass ratio of the carbon fiber fabric to the resin liquid is 2.9:1.
[0086] [Example 8]
[0087] 800 g of dicyclopentadiene, 132 g of a resin additive (comprising 120 g of ethylidene norbornene, 1 g of 5-vinylbicyclo[2.2.1]hept-2-ene, 10.5 g of styrene and 0.5 g of 2-methoxystyrene) and 60 g of an interface agent I (comprising 15 g of polytetrahydrofuran, 15 g of polypropylene glycol and 30 g of polydioxane) were fully mixed to prepare a uniform solution, thereby obtaining a modified dicyclopentadiene resin solution I;
[0088] Secondly, 243 g of dicyclopentadiene and 62 g of interface agent II (comprising 20 g of polymerized MDI, 40 g of 4,4-MDI and 2.0 g of cyclohexane-1,2-dicarboxylic acid diglycidyl ester) were fully mixed to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution II;
[0089] 0.075g 0.25 g of monobutyltin triisooctanoate, 5.7 g of diphenyl ether, and 0.8 g of tributyl phosphite were fully mixed to obtain a catalyst solution;
[0090] A demoulding cloth is first laid in the mold, and a T700-grade twill carbon fiber fabric is stacked on the demoulding cloth, the warp and weft yarn bundles of the carbon fiber fabric are 6k, and then a demoulding cloth is laid on the carbon fiber fabric again, and then the mold is closed, and nitrogen or argon is blown into the mold along the injection port to drive out the residual air in the mold; modified dicyclopentadiene resin liquid I, modified dicyclopentadiene resin liquid II, and catalyst solution are uniformly mixed to obtain a resin liquid, and the obtained resin liquid is injected into the mold cavity along the injection port, and then the temperature is raised to 150°C, and the temperature is kept for 2.5 hours to complete curing, and the carbon fiber-polydicyclopentadiene composite material is obtained by demoulding, wherein the mass ratio of the carbon fiber fabric to the resin liquid is 4.5:1.
[0091] [Example 9]
[0092] 1000 g of dicyclopentadiene, 66.5 g of a resin additive (comprising 55 g of ethylidene norbornene, 0.5 g of 5-vinylbicyclo[2.2.1]hept-2-ene, and 11 g of 1,3-diisopropenylbenzene) and 39 g of an interface agent I (comprising 20 g of ethylene glycol monoallyl ether, 10 g of polypropylene glycol, and 9 g of tert-butyl peroxybenzoate) were fully mixed to prepare a uniform solution, thereby obtaining a modified dicyclopentadiene resin solution I;
[0093] Secondly, 275 g of dicyclopentadiene and 49 g of interface agent II (comprising 24 g of polymerized XDI, 24 g of 2,4-TDI and 1.0 g of diglycidyl tetrahydrophthalate) were fully mixed to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution II;
[0094] 0.02g 0.08 g of dioctyltin monododecanoate, 0.7 g of phenylcyclopropane, 0.7 g of indane, and 0.25 g of tripropyl phosphite were fully mixed to obtain a catalyst solution;
[0095] A demoulding cloth is first laid in the mold, and a T300-grade satin carbon fiber fabric is stacked on the demoulding cloth, the warp and weft yarn bundles of the carbon fiber fabric are 12k, and then a demoulding cloth is laid on the carbon fiber fabric again, and then the mold is closed, and nitrogen or argon is blown into the mold along the injection port to drive out the residual air in the mold; modified dicyclopentadiene resin liquid I, modified dicyclopentadiene resin liquid II, and catalyst solution are uniformly mixed to obtain a resin liquid, and the obtained resin liquid is injected into the mold cavity along the injection port, and then the temperature is raised to 180°C, and the temperature is kept for 0.5 hours to complete curing, and the carbon fiber-polydicyclopentadiene composite material is obtained by demoulding, wherein the mass ratio of the carbon fiber fabric to the resin liquid is 2.7:1.
[0096] [Example 10]
[0097] 900 g of dicyclopentadiene, 107.2 g of a resin additive (comprising 100 g of ethylidene norbornene, 1.2 g of 5-vinylbicyclo[2.2.1]hept-2-ene, and 6 g of α-methylstyrene) and 72 g of an interface agent I (comprising 12 g of 2-hydroxyethyl acrylate, 12 g of 4-hydroxybutyl acrylate, 39 g of diisopropylbenzene peroxide, and 9 g of tert-butyl perbenzoate) were fully mixed to prepare a uniform solution, thereby obtaining a modified dicyclopentadiene resin solution I;
[0098] Secondly, 202 g of dicyclopentadiene and 61 g of interface agent II (comprising 40 g of polymerized MDI, 20 g of CHDI and 1.0 g of cyclohexane-1,2-dicarboxylic acid diglycidyl ester) were fully mixed to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution II;
[0099] 0.05g 0.25 g of dibutyltin di(isooctylmaleate), 1.9 g of benzocyclobutane, 0.7 g of indane, and 0.63 g of trimethyl phosphite were fully mixed to obtain a catalyst solution;
[0100] A demoulding cloth is first laid in the mold, and a T800-grade twill carbon fiber fabric is stacked on the demoulding cloth, the warp and weft yarn bundles of the carbon fiber fabric are 6k, and then a demoulding cloth is laid on the carbon fiber fabric again, and then the mold is closed, and nitrogen or argon is blown into the mold along the injection port to drive out the residual air in the mold; modified dicyclopentadiene resin liquid I, modified dicyclopentadiene resin liquid II, and catalyst solution are uniformly mixed to obtain a resin liquid, and the obtained resin liquid is injected into the mold cavity along the injection port, and then the temperature is raised to 160°C, and the temperature is kept for 1.5 hours to complete curing, and the carbon fiber-polydicyclopentadiene composite material is obtained by demoulding, wherein the mass ratio of the carbon fiber fabric to the resin liquid is 4.3:1.
[0101] [Comparative Example 1] Preparation of composite materials without adding interface agent
[0102] First, 1300 g of dicyclopentadiene and 131 g of a resin additive (comprising 130 g of ethylidene norbornene, 0.9 g of vinyl bicyclo[2.2.1]hept-2-ene, 10 g of 1,3-diisopropylbenzene and 0.1 g of 2-isopropoxystyrene) were fully mixed to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution;
[0103] 0.065g 1.80 g of diphenyl ether and 0.40 g of tritolyl phosphite were fully mixed to obtain a catalyst solution;
[0104] A release cloth is first laid in the mold, and a carbon fiber fabric is stacked on the release cloth. Then, a release cloth is laid on the carbon fiber fabric again. Then, the mold is closed, and nitrogen or argon is blown into the mold along the injection port to drive out the residual air in the mold. The modified dicyclopentadiene resin liquid and the catalyst solution are evenly mixed to obtain a resin liquid, and the obtained resin liquid is injected into the mold cavity along the injection port, and then the temperature is raised to 150°C, and the temperature is kept for 2 hours to complete the curing. The carbon fiber-polydicyclopentadiene composite material is demolded to obtain the carbon fiber fabric and the resin liquid. The mass ratio of the resin fabric to the resin liquid is 2.5:1.
[0105] [Comparative Example 2] Preparation of composite materials by adding only interface agent I
[0106] 1000 g of dicyclopentadiene, 131 g of a resin auxiliary (comprising 130 g of ethylidene norbornene, 0.9 g of vinyl bicyclo[2.2.1]hept-2-ene, 10 g of 1,3-diisopropylbenzene and 0.1 g of 2-isopropoxystyrene) and 68 g of an interface agent I (comprising 12 g of polyethylene glycol and 12 g of 5-norbornene-2-methanol, 39 g of diisopropyl peroxide and 5 g of dimethicone) were fully mixed to prepare a uniform solution, thereby obtaining a modified dicyclopentadiene resin solution;
[0107] 0.065g 1.80 g of diphenyl ether and 0.40 g of tritolyl phosphite were fully mixed to obtain a catalyst solution;
[0108] First, lay a release cloth in the mold, stack carbon fiber fabric on the release cloth, and then lay a release cloth on the carbon fiber fabric again, then close the mold, blow nitrogen or argon along the injection port to drive out the residual air in the mold; mix the modified dicyclopentadiene resin liquid and the catalyst solution evenly to obtain a resin liquid, inject the obtained resin liquid into the mold cavity along the injection port, then heat it to 150°C, keep it warm for 2.5 hours to complete curing, and demold to obtain a carbon fiber-polydicyclopentadiene composite material, wherein the mass ratio of the carbon fiber fabric to the resin liquid is 2.5:1.
[0109] [Comparative Example 3] Preparation of composite materials by adding only interface agent II
[0110] 1300g of dicyclopentadiene, 110.8g of resin additive (including 110g of ethylidene norbornene, 0.8g of vinyl bicyclo[2.2.1]hept-2-ene, 9.95g of 1,3-diisopropylbenzene and 0.05g of 2-isopropoxystyrene) and 61g of interface agent II (including 40g of polymerized MDI, 20g of 3,4-MDI and 1.0g of glycidyl methacrylate) were fully mixed to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution.
[0111] 0.065g 1.80 g of diphenyl ether and 0.40 g of tritolyl phosphite were fully mixed to obtain a catalyst solution;
[0112] First, lay a release cloth in the mold, stack carbon fiber fabric on the release cloth, and then lay a release cloth on the carbon fiber fabric again, then close the mold, blow nitrogen or argon along the injection port to drive out the residual air in the mold; mix the modified dicyclopentadiene resin liquid and the catalyst solution evenly to obtain a resin liquid, inject the obtained resin liquid into the mold cavity along the injection port, then heat it to 150°C, keep it warm for 2.5 hours to complete curing, and demold to obtain a carbon fiber-polydicyclopentadiene composite material, wherein the mass ratio of the carbon fiber fabric to the resin liquid is 2.5:1.
[0113] [Comparative Example 4] Epoxy resin carbon fiber composite material
[0114] First lay a release cloth in the mold, stack carbon fiber fabric on the release cloth, and then lay a release cloth on the carbon fiber fabric again, then close the mold, blow nitrogen or argon along the injection port to drive out the residual air in the mold; 100 parts of bisphenol A epoxy resin (epoxy equivalent 180-190, brand Nan Ya E-128) and 25 parts of DETDA curing agent (brand Jining Huakai E100) are mixed at 25°C for 60 seconds, injected into the mold cavity along the injection port, and then heated to 140°C and kept warm for 3 hours to complete curing. After complete curing, demould and take out the sample. The mass ratio of carbon fiber fabric to epoxy resin in the sample is 2.5:1.
[0115] [Experimental Example 1] Machinability of Composite Materials
[0116] The material composite material in Example 1 was processed using common machine tools, and the appearance of the material was photographed and analyzed and a simple load-bearing demonstration was performed.
[0117] like Figure 1 The following is a microscopic comparison of the cross section of the carbon fiber composite material after cutting. Figure 1 The left picture in the middle is a microscopic photograph of the cross section of the composite material prepared from the carbon fiber and commercial epoxy resin in Example 4, which has many defects and a loose fiber structure; the right picture is a microscopic photograph of the cross section of the composite material prepared from the carbon fiber and modified dicyclopentadiene resin solution in Example 1, which has few defects and a compact fiber structure. This shows that the interface between the resin solution and the carbon fiber of the present invention is well bonded and has few defects.
[0118] like Figure 2 The photo shows the sample of the carbon fiber composite material prepared in Example 1 of the present invention after drilling and tapping. It can be seen that the surface of the processed section of the composite material of the present invention is smooth, without tearing, delamination, wire drawing and the like. This shows that the composite material of the present invention is easy to machine and the appearance of the material after processing is intact. The punched material of the present invention has good mechanical strength after riveting. Figure 3 As shown, the riveted workpiece can bear the weight of a normal adult without deformation or damage. After the tapped sample of the present invention is fixed with bolts, it can bear the weight of 20 kg of barreled water without thread slippage or dislocation.
[0119] In addition to cutting, drilling and tapping, the composite material of the present invention can also be processed in a variety of other ways. Figure 4 As shown in the figure, the composite material is cut by a computer numerical control machine tool (CNC), and after simple grinding, a series of special-shaped parts of different shapes can be obtained, and the appearance of the material is intact without obvious damage. CNC engraving can mill the surface of the material to make a specific curved surface with a smooth surface and intact fiber texture without cracks.
[0120] [Experimental Example 2] Tensile properties and open-hole tensile properties test of composite materials
[0121] The composite materials prepared in Examples 1-10 and Comparative Examples 1-4 were tested for tensile properties according to ASTM D3039, and for open-hole tensile strength according to ASTM D5766. At least 5 specimens were tested for each group of the above tests, and the average value was calculated.
[0122]
[0123] Wherein comparative example 1 is polydicyclopentadiene / carbon fiber composite material, comparative example 2 is polydicyclopentadiene / carbon fiber composite material with only interface agent I added, comparative example 3 is polydicyclopentadiene / carbon fiber composite material with only interface agent II added, and comparative example 4 is epoxy resin / carbon fiber composite material. From the tensile strength data of several comparative examples, comparative example 4 has the greatest strength, while comparative example 1 has the least strength, mainly because the surface of commercialized carbon fiber composite material contains polar groups, high surface energy, high bonding force with high polar epoxy resin, high material composite uniformity, poor bonding force with dicyclopentadiene, and poor material composite uniformity. This situation will be improved after adding interface agent. But only after both types of interface agents are added (embodiments 1 to 10), the tensile properties of the material will be greatly improved (the lower performance of embodiment 7 is caused by the low carbon fiber content). After adding two types of interface agents, the alcohol substances in interface agent I and the isocyanate in interface agent II will undergo addition reaction under the action of catalyst, thereby improving the uniformity of bonding with carbon fiber composite material and improving the tensile properties of composite material. A similar rule is also observed when comparing the open-hole tensile strength. The open-hole tensile strength of the embodiments of the present invention is better than that of the epoxy resin / carbon fiber composite material, indicating that the introduction of the interface agent is beneficial to improving the machinability of the material.
[0124] [Experimental Example 3] Bending performance test of composite materials
[0125] The composite materials prepared in Examples 1-10 and Comparative Examples 1-4 were subjected to the three-point loading method according to ASTM D7264 to measure the bending properties of the composite materials. At least 5 specimens were tested for each group of the above tests, and the average value was calculated.
[0126]
[0127] Wherein comparative example 1 is a polydicyclopentadiene / carbon fiber composite material, comparative example 2 is a polydicyclopentadiene / carbon fiber composite material with only interface agent I added, comparative example 3 is a polydicyclopentadiene / carbon fiber composite material with only interface agent II added, and comparative example 4 is an epoxy resin / carbon fiber composite material. From the data of the bending modulus and bending strength of several comparative examples, the bending modulus and strength of comparative example 4 are the largest, while the modulus and strength of comparative example 1 are the smallest, only about half of the epoxy resin / carbon fiber composite material. This phenomenon is also caused by the small bonding force between carbon fiber and polydicyclopentadiene. Adding an interface agent will improve this situation. After adding two types of interface agents, the bending strength and modulus of Examples 1 to 10 (the lower performance of Example 7 is caused by the low carbon fiber content) are improved or even significantly improved. It shows that the interface agent added in the present invention is very helpful for improving the bending performance of polydicyclopentadiene / carbon fiber composite materials.
[0128] [Experimental Example 4] Interlaminar shear performance and notched impact strength test of composite materials
[0129] The composite materials prepared in Examples 1-10 and Comparative Examples 1-4 were tested for interlaminar shear strength according to the short beam shear (SBS) test method of ASTM D2344; and the notched impact strength of the composite materials was tested according to ISO 179-1:2010. At least 5 specimens were tested in each group, and the average value was calculated.
[0130]
[0131] Among them, Comparative Example 1 is a polydicyclopentadiene / carbon fiber composite material, Comparative Example 2 is a polydicyclopentadiene / carbon fiber composite material with only interface agent I added, Comparative Example 3 is a polydicyclopentadiene / carbon fiber composite material with only interface agent II added, and Comparative Example 4 is an epoxy resin / carbon fiber composite material. From the data of the interlaminar shear strength of several comparative examples, the interlaminar shear strength of Comparative Example 4 is the largest, while the interlaminar shear strength of Comparative Example 1 is the smallest, which is only about half of the epoxy resin / carbon fiber composite material. This phenomenon most directly reflects that the bonding force between carbon fiber and polydicyclopentadiene is less than the bonding force between carbon fiber and epoxy resin. It is also the main reason why we explore the addition of interface agents to change this disadvantage. It can be seen from Comparative Examples 2 and 3 that this situation will be significantly improved when an interface agent is added, especially when interface agent II is added, the epoxy component and isocyanate component therein will cross-link with the polar groups on the surface of the carbon fiber, significantly improving the interlaminar shear strength, and when two types of interface agents are used, the interlaminar shear of Examples 1 to 10 is significantly improved.
[0132] From the notched impact strength of several comparative examples, it can be seen that the notched impact strength of the epoxy resin / carbon fiber composite material (Comparative Example 4) is the lowest, while the notched impact strength of the polydicyclopentadiene / carbon fiber composite material is much greater than that of the epoxy resin / carbon fiber composite material. This is mainly because the epoxy resin itself is a brittle material (elongation at break <5%), while the polydicyclopentadiene we obtained is a tough material (elongation at break >30%). After being compounded with carbon fiber, the overall toughness of the material is improved, thereby significantly improving the notched impact performance of the composite material. After the introduction of the interface agent, the notched impact performance of the material will be further significantly improved due to the increased bonding between the resin and the carbon fiber.
[0133] [Experimental Example 5] Post-impact compression strength and open-hole compression strength performance test of composite materials
[0134] The composite materials prepared in Examples 1-10 and Comparative Examples 1-4 were characterized for their impact damage resistance by the residual compressive strength of the composite sheet containing impact damage according to ASTM D7136 and ASTM D7317 standards; and the open hole compressive strength of the composite materials was tested according to ASTM D6484 standard. At least 5 specimens were tested for each group of the above tests, and the average value was calculated.
[0135]
[0136] Among them, Comparative Example 1 is a polydicyclopentadiene / carbon fiber composite material, Comparative Example 2 is a polydicyclopentadiene / carbon fiber composite material with only interface agent I added, Comparative Example 3 is a polydicyclopentadiene / carbon fiber composite material with only interface agent II added, and Comparative Example 4 is an epoxy resin / carbon fiber composite material. Comparing the post-impact compression strength of several comparative examples, the post-impact compression strength of Comparative Example 4 is much higher than the post-impact compression strength of Comparative Example 1. This phenomenon is also caused by the small bonding force between carbon fiber and polydicyclopentadiene. Adding an interface agent will improve this situation. After adding two types of interface agents, the post-impact compression strength of Examples 1 to 10 (the lower performance of Example 7 is caused by the low carbon fiber content) is improved or even significantly improved. It shows that the interface agent added in the present invention is very helpful for improving the bending performance of polydicyclopentadiene / carbon fiber composite materials. Comparing the open hole compression strength, there is also a similar rule. The open hole compression strength of the embodiments of the present invention is better than that of epoxy resin / carbon fiber composite materials, which shows that the introduction of the interface agent is beneficial to improving the machinability of the material.
[0137] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various reasonable modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A carbon fiber-polydicyclopentadiene composite material with high notched impact strength, characterized in that: The composite material is compounded by a carbon fiber fabric and a resin liquid through a reaction molding process, wherein the mass ratio of the carbon fiber fabric to the resin liquid is (1.0-5.0):1; the resin liquid is prepared by mixing dicyclopentadiene, a resin auxiliary agent, an interface agent, a catalyst and a catalyst auxiliary agent.
2. The carbon fiber-polydicyclopentadiene composite material according to claim 1, characterized in that: The carbon fiber fabric is one or more of T300, T700, T800 grade carbon fiber cloth or carbon fiber cloth fiber bundles, and the warp and weft yarn bundles are 3k, 6k or 12k; the carbon fiber fabric is one or more of plain carbon fiber cloth, twill carbon fiber cloth or satin carbon fiber cloth.
3. The carbon fiber-polydicyclopentadiene composite material according to claim 1, characterized in that: The resin liquid contains 72.917wt%-90.931wt% of dicyclopentadiene, 4.205wt%-15.678wt% of resin additives, 2.162wt%-5.536wt% of interface agent I, 2.532wt%-5.833wt% of interface agent II, 0.005wt%-0.028wt% of catalyst, and 0.050wt%-0.500wt% of catalyst additive.
4. The carbon fiber-polydicyclopentadiene composite material according to claim 3, characterized in that: The resin additive includes 5-vinylbicyclo[2.2.1]hept-2-ene, ethylidene norbornene and phenyl olefin molecules; the mass ratio of the three is 1:(80-200):(5-20); the phenyl olefin molecules are one or more of the following structures: The R group is a C1-C6 alkyl group.
5. The carbon fiber-polydicyclopentadiene composite material according to claim 3, characterized in that: The interface agent I comprises an alcohol substance and an initiator, and the mass ratio of the two is 1:(0.3-3); the alcohol substance comprises one or more of the following structures, wherein the degree of polymerization of the polymer is n=5-50: The initiator is one or more of dioxane, polyoxane, and peroxide; the peroxide includes one or more of the following structures:
6. The carbon fiber-polydicyclopentadiene composite material according to claim 3, characterized in that: The interface agent II comprises an epoxy compound and an isocyanate, the mass ratio of the two being 1; (30-100); the epoxy compound comprises glycidyl methacrylate 4,5-Epoxytetrahydrophthalic acid diglycidyl ester Cyclohexane-1,2-dicarboxylic acid diglycidyl ester and diglycidyl tetrahydrophthalate One or more of the following; The isocyanate is one or more of the following structures:
7. The carbon fiber-polydicyclopentadiene composite material according to claim 3, characterized in that: The catalyst comprises a ruthenium complex and an organic tin compound, wherein the mass ratio of the two is 1:(0.1-5); the ruthenium complex comprises one or more of the following structures: The organotin compound comprises one or more of the following structures: The catalyst auxiliary agent comprises a retarder and a cosolvent, and the mass ratio of the retarder and the cosolvent is 1:(3-10); wherein the retarder is a phosphite molecule, specifically one or more of trimethyl phosphite, triethyl phosphite, tripropyl phosphite, tributyl phosphite, triphenyl phosphite or tritolyl phosphite; and the cosolvent is one or more of diphenyl ether, dihydroindane, indene, tetralin, trichlorobenzene, phenylcyclopropane and benzocyclobutane.
8. The method for preparing the carbon fiber-polydicyclopentadiene composite material according to claim 1, characterized in that: The following steps are involved: A1: taking a portion of dicyclopentadiene, resin additive and interface agent I and fully mixing them to prepare a uniform solution to obtain modified dicyclopentadiene resin solution I; A2 fully mixes the remaining dicyclopentadiene with the interface agent II to prepare a uniform solution to obtain a modified dicyclopentadiene resin solution II A3 fully mixes the catalyst, the cosolvent in the catalyst promoter and the retarder to obtain a catalyst solution; A4: First lay a release cloth in the mold, stack multiple layers of carbon fiber fabric on the release cloth, then lay another release cloth on the carbon fiber fabric, then close the mold, and blow nitrogen or argon along the injection port to drive out the residual air in the mold; A5: uniformly mix the modified dicyclopentadiene resin liquid I, the modified dicyclopentadiene resin liquid II and the catalyst solution to obtain a resin liquid, inject the obtained resin liquid into the mold cavity along the injection port, then heat it to 60-180° C., keep it warm for 0.5-8 hours to complete curing, and demold to obtain the carbon fiber-polydicyclopentadiene composite material.
9. The carbon fiber-polydicyclopentadiene composite material according to claim 1, characterized in that: The tensile strength of the composite material is 624-1092MPa; the flexural strength of the composite material is 603-840MPa; the flexural modulus of the composite material is 48-98GPa; the interlaminar shear strength of the composite material is 47-65MPa; the notched impact strength of the composite material is 68-169KJ m -2 ; The post-impact compressive strength of the composite material is 170-262MPa; the open-hole tensile strength of the composite material is 380-485MPa; the open-hole compressive strength of the composite material is 288-367MPa.
10. The use of the carbon fiber-polydicyclopentadiene composite material according to claim 1, characterized in that: Used in automobile, rail transportation, construction industry, aerospace, sporting goods, storage and packaging fields.